Advances in thiosemicarbazone metal complexes as anti-lung cancer agents - Bai, Xian-Guang; Zheng, Yunyun; Qi, Jinxu (Frontiers in Pharmacology, 2022)
The great success of cisplatin as a chemotherapeutic agent considerably increased research efforts in inorganic biochemistry to identify more metallic drugs having the potential of treating lung cancer. Metal coordination centres, which exhibit a wide range of coordination numbers and geometries, various oxidised and reduced states and the inherent ligand properties offer pharmaceutical chemists a plethora of drug structures. Owing to the presence of C=N and C=S bonds in a thiosemicarbazone Schiff base, N and S atoms in its hybrid orbital has lone pair of electrons, which can generate metal complexes with different stabilities with most metal elements under certain conditions. Such ligands and complexes play key roles in the treatment of anti-lung cancer. Research regarding metallic anti-lung cancer has advanced considerably, but there remain several challenges. In this review, we discuss the potential of thiosemicarbazone Schiff base complexes as anti-lung cancer drugs, their anti-cancer activities and the most likely action mechanisms involving the recent families of copper, nickel, platinum, ruthenium and other complexes.